RANCANG BANGUN SISTEM CONTROLLING PENYIRAMAN TANAMAN KANGKUNG BERBASIS INTERNET OF THINGS - Anes Inda Rabbika; MH Nugraha; Abd Rohman; Widyantoro; Tatakostaman; Willy Muhamad Fauzi; Asep Mustofa; Tri Jaya Widagdo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Kankung is a type of plant that is classified as a vegetable and is grown as food. The Mandiri Jaya Flowering Farmers Group in Cikupa Village, Karangnunggal has 9 blocks of farmland that are planted with kankung plants as one of the incomes of the farmers. The distribution of water to water spinach plants should be even and regular. For watering water spinach, 20 liters of water is needed, which is done manually by carrying water on the back and then watering the water spinach repeatedly. It is important to water kangkung plants regularly, once in the morning and once in the evening. Watering kangkung (a type of water spinach) is an important part of maintaining the plant, as it needs a sufficient supply of water to carry out photosynthesis and obtain the nutrients it needs to grow and develop. To support the automation process so that production factors can be achieved, a control system is required. One type of controller that is well-suited for use is a microcontroller. The researcher designed a Kangkung Plant Irrigation System Based on the Internet of Things to address the issues mentioned above. Farmers control the irrigation of watercress using smartphones, which makes their work easier and more efficient.